2012
DOI: 10.1021/ic302191d
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Structure and Properties of the Na2CoP2O7 Pyrophosphate Cathode for Sodium-Ion Batteries: A Supersuperexchange-Driven Non-Collinear Antiferromagnet

Abstract: The crystal and magnetic structure and properties of the Na(2)CoP(2)O(7) Na(+)-ion battery cathode material have been characterized by magnetic susceptibility, specific heat, and variable-temperature neutron powder diffraction measurements. Na(2)CoP(2)O(7) crystallizes in the orthorhombic space group Pna2(1) with a = 15.4061(3) Å, b = 10.28854(9) Å, and c = 7.70316(15) Å, having a layered structure with slabs of [CoP(2)O(7)](∞) separated by Na cations. The magnetic property measurements and neutron diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 29 publications
(47 reference statements)
4
48
0
Order By: Relevance
“…In addition to Na 2 MnP 2 O 7 , Na 2 CoP 2 O 7 was also investigated as a high voltage cathode 178, 179, 180. Yamada's group reported an orthorhombic structure Na 2 CoP 2 O 7 with the space group of Pna 2 1 , which offered a two‐dimensional Na‐diffusion pathway and could deliver a reversible discharge capacity of 80 mAh g –1 at an average potential of 3 V 178.…”
Section: Pyrophosphate Materials For Na Storagementioning
confidence: 99%
“…In addition to Na 2 MnP 2 O 7 , Na 2 CoP 2 O 7 was also investigated as a high voltage cathode 178, 179, 180. Yamada's group reported an orthorhombic structure Na 2 CoP 2 O 7 with the space group of Pna 2 1 , which offered a two‐dimensional Na‐diffusion pathway and could deliver a reversible discharge capacity of 80 mAh g –1 at an average potential of 3 V 178.…”
Section: Pyrophosphate Materials For Na Storagementioning
confidence: 99%
“…Na 2 CoP 2 O 7 can yield a reversible capacity of about 80 mA h g −1 at ca. 2-4 V versus Na/Na + [63,64]. Although a high initial discharge specific capacity can normally be achieved for the phosphates polyanions, the unstable structure results in relatively poor cycling performances.…”
Section: Pyrophosphate Materialsmentioning
confidence: 99%
“…[145] Pyrophosphate Na 2 MP 2 O 7 (M = Fe, Mn, Co) has recently been suggested as a possible electroactive cathode material for SIBs. [146] The robust and stable 3D (P 2 O 7 ) 4 framework can facilitate the Na + accommodation, and the abundance of the crystal configuration of Na 2 MP 2 O 7 can also provide a series of opportunities to host the Na + insertion/extraction with a notably wide redox potential range from 2.0 V to 4.9 V. [146,147] It is suggested that Na 2 CoP 2 O 7 has three polymorphs including orthorhombic, tetragonal, and triclinic phases. Orthorhombic (Pna21) or tetragonal Na 2 CoP 2 O 7 is a layered structure with [Co(P 2 O 7 )] 2− layers constructed from oxygen-linked CoO 4 tetrahedra and their four surrounding P 2 O 7 units, offering continuous channels for Na + transportation and thus efficient Na + (de-)intercalation.…”
Section: Pyrophosphatesmentioning
confidence: 99%
“…Orthorhombic (Pna21) or tetragonal Na 2 CoP 2 O 7 is a layered structure with [Co(P 2 O 7 )] 2− layers constructed from oxygen-linked CoO 4 tetrahedra and their four surrounding P 2 O 7 units, offering continuous channels for Na + transportation and thus efficient Na + (de-)intercalation. [146] Although the triclinic polymorph has also been predicted to be a redox-active material, the thermodynamic instability greatly limits its utilization as a cathode material for SIBs. Recently, a stable triclinic polymorph, Na 2−x CoP 2 O 7 , has been successfully synthesized based on a Na-deficiencies-stabilization strategy, which showed an average potential of ≈4.3 V (vs Na + /Na) with three plateaus at 3.95 V, 4.33 V, and 4.43 V and delivered a reversible and stable capacity of ≈80 mA h g −1 at C/20, exhibiting an enhanced energy density of 344 W h kg −1 compared to the orthorhombic case (240 W h kg −1 ).…”
Section: Pyrophosphatesmentioning
confidence: 99%